Canada : Selected Issues. (IMF Staff Country Reports; Country Report, 1999)
This Selected Issues paper reviews empirical evidence on the main determinants of the real bilateral exchange rate between the Canadian and the U.S. dollars, with particular emphasis on the role played by cyclical and longer-term economic factors. The paper aims to identify the nature of the shocks that have contributed to the recent downward trend in the Canadian dollar. The analysis shows that fluctuations in the real bilateral exchange rate can be explained reasonably well by its long-term fundamentals. The paper also analyzes inflation and the natural rate of unemployment in Canada.